Introducing Interlaminar Full-Endoscopic Lumbar Diskectomy: A Critical Analysis of Complications, Recurrence Rates, and Outcome in View of Two Spinal Surgeons' Learning Curves - Joswig, Holger; Richter, Heiko; Haile, Sarah Roberta; Hildebrandt, Gerhard; Fournier, Jean-Yves (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background and Study Objective Interlaminar full-endoscopic diskectomy is a minimally invasive surgical alternative to microdiskectomy for the treatment of lumbar disk herniation. The authors analyze their surgical results and learning curves during and after the introductory phase of this surgical technique.Patients and Methods We present a case review of 76 patients operated on using interlaminar full-endoscopic diskectomy. We retrospectively analyzed two spinal surgeons' learning curves in terms of operation time with respect to intraoperative blood loss, conversion rates, complications, infections, length of hospitalization, need for rehabilitation, recurrence rates, pain intensity, and opioid use. Patients' functional status and Health-related Quality of Life were assessed by follow-up questionnaires for 47 patients, using the North American Spine Society Score and the Short Form 12 in addition to long-term pain intensity, work capacity, and patient satisfaction with the operation.Results A steady state of the learning curve (operation time) of an experienced spinal surgeon was reached after 40 cases. Supervision by a more experienced surgeon can shorten the learning curve. The rate of conversions (10%), complications (5%), and recurrent lumbar disk herniations (28%) did not negatively affect the long-term outcome in patients operated on before and after the learning phase. Patient satisfaction was high.Conclusions The rate of conversions, complications, and recurrent lumbar disk herniations compared with microdiskectomy combined with the challenging learning curve should be considered before surgeons adopt this procedure. Supervision by an endoscopically experienced spinal surgeon during the introductory phase is highly advisable.
Keywords: full-endoscopic lumbar diskectomy; learning curve; minimally invasive; percutaneous endoscopic lumbar diskectomy; recurrence rate